IMAGE ASPECTS OF NA ELONGATED STYLOID PROCESS: CASE REPORT (REMUNOM, 2025)
The elongation of the styloid process is a rarely encountered anomaly known as Eagle Syndrome, first described in 1937. The most common symptom is cervical pain. Therefore, accurate diagnosis is of utmost importance to ensure appropriate intervention, and recognizing the imaging features of this condition is essential. The objective of this study is to report a case of Eagle Syndrome and to contribute to the proper analysis of its radiographic aspects, as well as to highlight the importance of imaging examinations in providing the most effective treatment and supporting differential diagnosis. We describe the case of a 48-year-old male presenting with symptoms worsened by the condition, including orofacial pain and limited head movement. It is concluded that imaging exams such as panoramic radiography, posteroanterior and lateral skull projections, and computed tomography were effective in identifying the elongated styloid process.